High-capacity low-gas-yield ternary material and preparation method and application thereof
By controlling the concentration and feeding speed of ammonia aqueous solution in a gradient manner, combining high-priced elements and alumina coating, ternary material particles with gradient distribution are prepared, which solves the gas production problem of high-nickel content materials and achieves low gas production and high energy The balance of density improves the circulation and safety performance of the material.
Patent Information
- Application Number
- CN202411373984.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-10
AI Technical Summary
When the nickel content of existing ternary materials is higher than 60%, especially above 80%, gas production problems are serious, which affects safety performance and circulation performance, and methods to increase energy density will reduce the energy density of the material.
By controlling the concentration and feeding speed of ammonia aqueous solution in a gradient manner, controlling the reaction time, ternary material particles with gradient distribution are prepared, combining the coating of high-valent elements and alumina to form a core and shell structure, reducing gas production and improving gas production Surface stability.
It achieves the balance of low gas production and high energy density of ternary materials with high nickel content, and improves the circulation and safety performance of the materials.
Smart Images

Figure BDA0005068261930000121 
Figure HDA0005068261940000011
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a high-capacity, low-gas-generating ternary material and a preparation method and application thereof. Background Art
[0002] With the accelerated development of the electric vehicle industry, the research on lithium-ion batteries has also received more and more attention, and the performance requirements and technical requirements are getting higher and higher; ternary materials are increasingly used in electric vehicles and small power fields due to their high capacity, excellent performance and moderate price; however, with the increasing requirements for energy density, the nickel content of ternary materials needs to be further increased. When the nickel content is higher than 60%, especially when it reaches more than 80%, the gas production problem of the material is aggravated, the safety performance is reduced, and the cycle performance is further deteriorated.
[0003] Related technologies mostly reduce gas production by mixing single crystal particles or increasing the amount of material coating, but both methods will reduce the energy density of the material. Therefore, it is very important to provide a material with high nickel content, which can reduce gas production and effectively ensure high energy density. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a method for preparing a high-capacity and low-gas-producing ternary material, wherein the prepared ternary material not only has low gas production but also has high energy density.
[0005] The present invention also provides a ternary material prepared by the above preparation method.
[0006] The present invention also provides a positive electrode sheet comprising the above ternary material.
[0007] The present invention also provides the use of the above-mentioned ternary material or the above-mentioned positive electrode plate in a lithium-ion battery.
[0008] A method for preparing a ternary material according to a first aspect of an embodiment of the present invention comprises the following steps:
[0009] S1. Adding an aqueous ammonia solution into a solution containing a nickel source, a cobalt source, a manganese source and a hydroxide source, and performing solid-liquid separation after the reaction to obtain a precursor;
[0010] In the reaction, during the reaction time period of 0 to 1h, the feed rate is controlled to be 5mL / min to 10mL / min, and the concentration of ammonia water is 15% to 20%; during the reaction time period of 1h to 10h, the feed rate is controlled to be 2mL / min to 5mL / min, and the concentration of ammonia water is 5% to 10%; during the reaction time period of 10h to 36h, the feed rate is controlled to be 0.8mL / min to 1.2mL / min, and the concentration of ammonia water is 1% to 3%;
[0011] S2, mixing the precursor with a lithium source and a first transition metal element source and performing a first sintering treatment to obtain a sintered product;
[0012] The first transition metal element source includes at least one of a yttrium source, a niobium source, a molybdenum source, and a tungsten source;
[0013] S3, mixing the first sintered product with alumina and performing a second sintering treatment to obtain the ternary material.
[0014] The preparation method according to the embodiment of the present invention has at least the following beneficial effects:
[0015] The preparation method of the embodiment controls the concentration of the complexing agent (ammonia solution), the feed rate and the reaction time by gradient, thereby ensuring the gradient distribution of the primary particle size of the ternary material from the inside to the outside. Ammonia solution is used to control the grain growth rate. The lower the ammonia concentration, the slower the feed rate and the larger the primary particle size formed. - Used to precipitate transition metal cations.
[0016] According to some embodiments of the present invention, the reaction temperature of step S1 is 500°C to 1000°C. For example, it may be 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C or 1000°C.
[0017] According to some embodiments of the present invention, the first transition metal element source includes a yttrium source, a niobium source, a molybdenum source, and a tungsten source. The molar ratio of the yttrium source, the niobium source, the molybdenum source, and the tungsten source is 0.3 to 7:1:1:1. For example, the molar ratio of the yttrium source, the niobium source, the molybdenum source, and the tungsten source can be 0.3:1:1:1, 0.5:1:1:1, 0.7:1:1:1, 1:1:1:1, 2:1:1:1, 3:1:1:1, 4:1:1:1, 5:1:1:1, 6:1:1:1, or 7:1:1:1.
[0018] According to some embodiments of the present invention, in step S3, the mixed preparation raw materials further include a second transition metal element source.
[0019] According to some embodiments of the present invention, the second transition metal element source includes at least one of a yttrium source, a niobium source, a molybdenum source, and a tungsten source. The second transition metal element source may be the same as or different from the first transition metal element source.
[0020] According to some embodiments of the present invention, in the first transition metal element source and / or the second transition metal element source, the yttrium source includes yttrium oxide.
[0021] According to some embodiments of the present invention, in the first transition metal element source and / or the second transition metal element source, the niobium source includes at least one of niobium oxide and niobium hydroxide. The niobium oxide includes at least one of niobium monoxide, niobium dioxide, niobium trioxide, and niobium pentoxide. In the preparation process of the ternary material, there is no obvious difference between different niobium oxides or niobium hydroxides, and it is only necessary to ensure that the amount of niobium added is the same.
[0022] According to some embodiments of the present invention, in the first transition metal element source and / or the second transition metal element source, the molybdenum source includes molybdenum oxide. The molybdenum oxide includes at least one of molybdenum trioxide and molybdenum dioxide. In the preparation process of the ternary material, there is no obvious difference between different molybdenum oxides, and it is only necessary to ensure that the amount of molybdenum added is the same.
[0023] According to some embodiments of the present invention, in the first transition metal element source and / or the second transition metal element source, the tungsten source includes at least one of tungsten oxide and tungsten hydroxide. The tungsten oxide includes at least one of tungsten trioxide and tungsten dioxide. In the preparation process of the ternary material, there is no obvious difference between different tungsten oxides, and it is only necessary to ensure that the amount of tungsten added is the same.
[0024] According to some embodiments of the present invention, the molar ratio of the second transition metal source to the first transition metal source is 0.2 to 2.5. For example, the molar ratio of the second transition metal to the first transition metal can be 0.2, 0.4, 0.6, 0.8, 1, 1.2, 1.4, 1.6, 1.8, 2, 2.2, 2.4 or 2.5. This design of gradient distribution of high-valent elements can ensure that the amount of transition elements in the shell is high enough, which can better delay gas production and improve surface stability. At the same time, the transition element content of the core is low enough not to deteriorate the capacity.
[0025] According to some embodiments of the present invention, in the ternary material, the molar ratio of the first transition metal element to the manganese element is 0.01 to 0.3. For example, the molar ratio can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.2, 0.25 or 0.3. Thus, the cycle performance and gas production can be taken into account. When the molar ratio of the element feed is too high, it means that the proportion of high-valent elements is too high and the proportion of manganese elements is low, which will deteriorate the structural stability and cycle performance of the bulk phase; when the molar ratio of the element feed is less than 0.01, it means that the high-valent elements are too low, which cannot stabilize the surface and reduce the gas production.
[0026] According to some embodiments of the present invention, in the ternary material, the molar ratio of the Ni element to the total transition metal elements is ≥ 0.6. If the Ni content is too low, the gram capacity of the material will be low.
[0027] According to some embodiments of the present invention, the content of transition metal elements in the ternary material increases from the inside to the outside.
[0028] According to some embodiments of the present invention, the nickel content in the ternary material is greater than 60%, for example, 60%, 65%, 70%, 75%, 80%, 85%, 90% or 95%.
[0029] According to some embodiments of the present invention, the precursor is nickel cobalt manganese hydroxide. The nickel cobalt manganese hydroxide is Ni x Co y Mn z (OH)2; wherein 0.6≤x≤0.95, 0.04≤y≤0.39, 0.01≤z≤0.30, (x+y+z)=1. For example, Ni 0.83 Co 0.12 Mn 0.05 (OH)2.
[0030] According to some embodiments of the present invention, the nickel-cobalt-manganese hydroxide is Ni x Co y Mn z (OH)2; wherein, 0.8≤x≤0.95, 0.04≤y≤0.19, 0.01≤z≤0.15, (x+y+z)=1.
[0031] According to some embodiments of the present invention, the hydroxide source includes at least one of sodium hydroxide and potassium hydroxide.
[0032] According to some embodiments of the present invention, the nickel source includes at least one of nickel sulfate, nickel acetate, and nickel nitrate.
[0033] According to some embodiments of the present invention, the cobalt source includes at least one of cobalt sulfate, cobalt acetate, and cobalt nitrate.
[0034] According to some embodiments of the present invention, the manganese source includes at least one of manganese sulfate, manganese acetate, and manganese nitrate.
[0035] According to some embodiments of the present invention, the lithium source includes at least one of lithium hydroxide, lithium carbonate, and lithium nitrate.
[0036] According to some embodiments of the present invention, the molar ratio of the precursor to the lithium source is 1:1.05-1.2, for example, 1:1.05, 1:1.07, 1:1.1, 1:1.12, 1:1.14, 1:1.16, 1:1.18 or 1:1.2.
[0037] According to some embodiments of the present invention, the first sintering treatment comprises sequentially treating at 250°C to 350°C (such as 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, 310°C, 320°C, 330°C, 340°C or 350°C) for 1h to 3h (such as 1h, 1.5h, 2h or 2.5h, 3h), 450°C to 550°C (such as 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, 520°C, 530°C, 540°C or 550°C) for 1h to 3h (such as 1h, 1.5h, 2h or 2.5h, 3h), 450°C to 550°C (such as 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, 520°C, 530°C The method comprises the following steps: treating at 0℃, 510℃, 520℃, 530℃, 540℃ or 550℃ for 4h to 6h (such as 4h, 4.5h, 5h or 5.5h, 6h); treating at 750℃ to 850℃ (such as 750℃, 760℃, 770℃, 780℃, 790℃, 800℃, 810℃, 820℃, 830℃, 840℃ or 850℃) for 14h to 16h (such as 14h, 14.5h, 15h or 15.5h, 16h).
[0038] According to some embodiments of the present invention, the second sintering treatment includes sequentially treating at 450°C to 550°C (such as 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, 520°C, 530°C, 540°C or 550°C) for 9h to 11h (such as 9h, 9.5h, 10h or 10.5h, 11h) and 150°C to 250°C (such as 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C or 250°C) for 3h to 5h (such as 3h, 3.5h, 4h or 4.5h, 5h).
[0039] Gradient distribution of particle size can be achieved through staged sintering.
[0040] According to some embodiments of the present invention, the molar ratio of the aluminum element to the manganese element in the alumina is 0.01 to 0.05, for example, 0.01, 0.02, 0.03, 0.04 or 0.05.
[0041] The high-capacity and low-gas-generating ternary material according to the second aspect of the present invention is prepared by the preparation method described in the first aspect of the present invention.
[0042] According to some embodiments of the present invention, the ternary material includes a core body and a shell layer arranged on the surface of the core body; the ratio of the primary particle size of the shell layer to the primary particle size of the core body is 5-20.
[0043] The ternary material according to the embodiment of the present invention has at least the following beneficial effects:
[0044] Ternary materials refer to Li-containing layered transition oxides containing Ni, Co, and Mn elements. Among them, Ni provides high gram capacity, Co provides a certain capacity while ensuring rate performance, and Mn plays a role in supporting the layered structure to ensure structural stability. After transition metal elements (such as Y, Nb, Mo, and W) are added to the ternary material, the kinetic properties and gram capacity of the material can be improved. At the same time, these elements also have the function of fixing oxygen, thereby slowing down gas production; in order to further improve the cyclic performance of the material, the present invention adds a coating of aluminum oxide to the surface of the shell.
[0045] In addition, the smaller the primary particle size of the material, the better the gram capacity and kinetic performance, but the worse the cycle performance and the more serious the gas production, and this failure often starts from the shell of the material. The present invention ensures that the shell has sufficient structural stability by controlling the particle size of the shell to be larger than the particle size of the core (5 to 20), while the core, which is not so prone to failure, has a small particle size, which ensures the kinetic performance and gram capacity of the material. Through such a comprehensive design, the gas production of the material is improved, so that the ternary material has the characteristics of high capacity and low gas production.
[0046] Among transition metals, compared with Nb, Mo, and W, element Y has a better effect on improving gram capacity and circulation / gas production.
[0047] According to some embodiments of the present invention, the ternary material further includes an intermediate layer disposed between the core and the shell.
[0048] According to some embodiments of the present invention, the primary particle size of the ternary material is distributed from small to large from the core to the shell.
[0049] A positive electrode plate according to the third embodiment of the present invention comprises the ternary material as described in the second embodiment. Since the positive electrode plate adopts all the technical solutions of the ternary material of the above embodiment, it has at least all the beneficial effects brought by the technical solutions of the above embodiment.
[0050] According to the fourth aspect of the present invention, the above-mentioned ternary material is used in lithium-ion batteries.
[0051] According to some embodiments of the present invention, the above-mentioned ternary material is specifically used as an active substance of a positive electrode material in a lithium-ion battery.
[0052] According to some embodiments of the present invention, the lithium-ion battery includes a positive electrode sheet, a negative electrode sheet, and a separator located between the positive and negative electrode sheets.
[0053] According to some embodiments of the present invention, the positive electrode plate includes the ternary material.
[0054] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] Figure 1 It is a schematic diagram of the structure of the ternary material of Example 1 of the present invention. DETAILED DESCRIPTION
[0056] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0057] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0058] In the description of the present invention, if there is a description of first, second, etc., it is only for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.
[0059] In the description of the present invention, it should be noted that, unless otherwise clearly defined, words such as “setting” should be understood in a broad sense, and technicians in the relevant technical field can reasonably determine the specific meaning of the above words in the present invention in combination with the specific content of the technical solution.
[0060] In the description of the present invention, the terms "include" and "have" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or apparatus comprising a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to these processes, methods, products or apparatuses.
[0061] In the following embodiments, there are the following definitions:
[0062] The core refers to the inner side of the ternary material, and the shell refers to the outer side of the core of the ternary material. There is a fused middle layer between the shell and the core, and the depth of the middle layer is related to the calcination temperature and time in the actual preparation process.
[0063] The first transition metal element used to prepare the core is collectively referred to as X1; the second transition metal element used to prepare the shell is collectively referred to as X2.
[0064] The primary particle size of the core is D1; the primary particle size of the shell is D2.
[0065] Unless otherwise specified, the concentrations of the nickel sulfate solution, cobalt sulfate solution, manganese sulfate solution and sodium hydroxide solution used in the present invention are all 0.1 mol / L.
[0066] Example 1
[0067] This embodiment provides a ternary material. The structural schematic diagram of the ternary material is as follows Figure 1 As shown, Figure 1 It is only used as a structural representation and should not be understood as an actual proportional relationship. The preparation method of the ternary material is as follows:
[0068] S1. Precursor synthesis:
[0069] Mix nickel sulfate solution, cobalt sulfate solution, manganese sulfate solution and sodium hydroxide solution according to Ni 0.83 Co 0.12 Mn 0.05 (OH)2 was added to the reactor in a stoichiometric ratio; at the same time, an ammonia solution was introduced into the reactor, and the reaction temperature was 750°C. After reacting for 36 hours, the obtained slurry was separated into solid and liquid and dried to obtain the precursor Ni 0.83 Co 0.12 Mn 0.05 (OH)2.
[0070] The reaction process is as follows: in the reaction time period of 0 to 1 h, the feed rate is controlled to be 5 mL / min and the ammonia concentration is 10%; in the reaction time period of 1 h to 10 h, the feed rate is controlled to be 2 mL / min and the ammonia concentration is 5%; in the reaction time period of 10 h to 36 h, the feed rate is controlled to be 1 mL / min and the ammonia concentration is 2%.
[0071] S2, first sintering:
[0072] The precursor obtained in step S1 is mixed with lithium hydroxide and yttrium oxide, and sintered at 300° C. for 2 h, 500° C. for 5 h, and 800° C. for 15 h, respectively, to obtain a sintered product.
[0073] The molar ratio of the precursor to lithium hydroxide is 1:1, and the molar ratio of Y / Mn is 0.05.
[0074] S3, second sintering:
[0075] The sintered product obtained in step S2 is mixed with alumina to ensure that the molar ratio of Al / Mn is 0.02, and then sintered at 500° C. for 10 h and 200° C. for 4 h to obtain a ternary material.
[0076] After characterization, D2 / D1=5.
[0077] Example 2
[0078] This embodiment provides a ternary material. The preparation method of the ternary material is basically the same as that of embodiment 1, except that the reaction process of step S1 is different. The details are as follows:
[0079] The reaction process of step S1 is as follows: in the reaction time period of 0 to 1 h, the feed rate is controlled to be 8 mL / min and the ammonia concentration is 15%; in the reaction time period of 1 h to 10 h, the feed rate is controlled to be 5 mL / min and the ammonia concentration is 10%; in the reaction time period of 10 h to 36 h, the feed rate is controlled to be 1 mL / min and the ammonia concentration is 2%.
[0080] It has been characterized that D2 / D1=10.
[0081] Example 3
[0082] This embodiment provides a ternary material. The preparation method of the ternary material is basically the same as that of embodiment 1, except that the reaction process of step S1 is different. The details are as follows:
[0083] The reaction process of step S1 is as follows: in the reaction time period of 0 to 1 h, the feed rate is controlled to be 10 mL / min and the ammonia concentration is 20%; in the reaction time period of 1 h to 10 h, the feed rate is controlled to be 5 mL / min and the ammonia concentration is 10%; in the reaction time period of 10 h to 36 h, the feed rate is controlled to be 1 mL / min and the ammonia concentration is 2%.
[0084] It was characterized that D2 / D1=20.
[0085] Example 4
[0086] This embodiment provides a ternary material. The preparation method of the ternary material is basically the same as that of Embodiment 2, except that step S2 is different. The details are as follows:
[0087] S2, first sintering:
[0088] The precursor obtained in step S1 is mixed with lithium hydroxide, yttrium oxide, niobium oxide, molybdenum oxide and tungsten oxide, and sintered at 300° C. for 2 h, 500° C. for 5 h and 800° C. for 15 h in sequence to obtain a sintered product.
[0089] Among them, the molar ratio of the precursor to lithium hydroxide is 1:1, the molar ratio of (Y+Nb+Mo+W) / Mn is 0.05, and Y:Nb:Mo:W=0.7:0.1:0.1:0.1.
[0090] It has been characterized that D2 / D1=10.
[0091] Example 5
[0092] This embodiment provides a ternary material. The preparation method of the ternary material is basically the same as that of Embodiment 2, except that step S2 is different. The details are as follows:
[0093] S2, first sintering:
[0094] The precursor obtained in step S1 is mixed with lithium hydroxide, yttrium oxide, niobium oxide, molybdenum oxide and tungsten oxide, and sintered at 300° C. for 2 h, 500° C. for 5 h and 800° C. for 15 h in sequence to obtain a sintered product.
[0095] Among them, the molar ratio of the precursor to lithium hydroxide is 1:1, the molar ratio of (Y+Nb+Mo+W) / Mn is 0.05, and Y:Nb:Mo:W=0.1:0.3:0.3:0.3.
[0096] It has been characterized that D2 / D1=10.
[0097] Example 6
[0098] This embodiment provides a ternary material. The preparation method of the ternary material is basically the same as that of Embodiment 2, except that step S3 is different. The details are as follows:
[0099] S3, second sintering:
[0100] The sintered product obtained in step S2 is mixed with alumina to ensure that the molar ratio of Al / Mn is 0.01, and then sintered at 500° C. for 10 h and 200° C. for 4 h to obtain a ternary material.
[0101] It has been characterized that D2 / D1=10.
[0102] Example 7
[0103] This embodiment provides a ternary material. The preparation method of the ternary material is basically the same as that of Embodiment 2, except that step S3 is different. The details are as follows:
[0104] S3, second sintering:
[0105] The sintered product obtained in step S2 is mixed with alumina to ensure that the molar ratio of Al / Mn is 0.05, and then sintered at 500° C. for 10 h and 200° C. for 4 h to obtain a ternary material.
[0106] It has been characterized that D2 / D1=10.
[0107] Example 8
[0108] This embodiment provides a ternary material. The preparation method of the ternary material is basically the same as that of Embodiment 2, except that step S3 is different. The details are as follows:
[0109] S3, second sintering:
[0110] The sintered product obtained in step S2 is mixed with alumina and yttrium oxide to ensure that the molar ratio of Al / Mn is 0.02 and the molar ratio of X2 / X1 is 1.5, and then sintered at 500°C for 10 hours and 200°C for 4 hours to obtain a ternary material.
[0111] It has been characterized that D2 / D1=10.
[0112] Example 9
[0113] This embodiment provides a ternary material. The preparation method of the ternary material is basically the same as that of Embodiment 2, except that step S3 is different. The details are as follows:
[0114] S3, second sintering:
[0115] The sintered product obtained in step S2 is mixed with alumina and yttrium oxide to ensure that the molar ratio of Al / Mn is 0.02 and the molar ratio of X2 / X1 is 2.0, and then sintered at 500°C for 10 hours and 200°C for 4 hours to obtain a ternary material.
[0116] It has been characterized that D2 / D1=10.
[0117] Example 10
[0118] This embodiment provides a ternary material. The preparation method of the ternary material is basically the same as that of Embodiment 2, except that step S3 is different. The details are as follows:
[0119] S3, second sintering:
[0120] The sintered product obtained in step S2 is mixed with alumina and yttrium oxide to ensure that the molar ratio of Al / Mn is 0.02 and the molar ratio of X2 / X1 is 2.5, and then sintered at 500°C for 10 hours and 200°C for 4 hours to obtain a ternary material.
[0121] It has been characterized that D2 / D1=10.
[0122] Embodiment 11
[0123] This embodiment provides a ternary material. The preparation method of the ternary material is basically the same as that of Embodiment 2, except that step S2 is different. The details are as follows:
[0124] S2, first sintering:
[0125] The precursor obtained in step S1 is mixed with lithium hydroxide and yttrium oxide, and sintered at 300° C. for 2 h, 500° C. for 5 h, and 800° C. for 15 h, respectively, to obtain a sintered product.
[0126] The molar ratio of the precursor to lithium hydroxide is 1:1, and the molar ratio of Y / Mn is 0.01.
[0127] It has been characterized that D2 / D1=10.
[0128] Example 12
[0129] This embodiment provides a ternary material. The preparation method of the ternary material is basically the same as that of Embodiment 2, except that step S2 is different. The details are as follows:
[0130] S2, first sintering:
[0131] The precursor obtained in step S1 is mixed with lithium hydroxide and yttrium oxide, and sintered at 300° C. for 2 h, 500° C. for 5 h, and 800° C. for 15 h, respectively, to obtain a sintered product.
[0132] The molar ratio of the precursor to lithium hydroxide is 1:1, and the molar ratio of Y / Mn is 0.2.
[0133] It has been characterized that D2 / D1=10.
[0134] Example 13
[0135] This embodiment provides a ternary material. The preparation method of the ternary material is basically the same as that of Embodiment 2, except that step S2 is different. The details are as follows:
[0136] S2, first sintering:
[0137] The precursor obtained in step S1 is mixed with lithium hydroxide and yttrium oxide, and sintered at 300° C. for 2 h, 500° C. for 5 h, and 800° C. for 15 h, respectively, to obtain a sintered product.
[0138] The molar ratio of the precursor to lithium hydroxide is 1:1, and the molar ratio of Y / Mn is 0.3.
[0139] It has been characterized that D2 / D1=10.
[0140] Embodiment 14
[0141] This embodiment provides a ternary material. The preparation method of the ternary material is basically the same as that of Embodiment 2, except that the stoichiometric ratio of the reaction raw materials in step S1 is different. The details are as follows:
[0142] S1. Precursor synthesis:
[0143] Mix nickel sulfate solution, cobalt sulfate solution, manganese sulfate solution and sodium hydroxide solution according to Ni 0.5 Co 0.2 Mn 0.3 (OH)2 was added to the reactor in a stoichiometric ratio; at the same time, an ammonia solution was introduced into the reactor. After reacting for 36 hours, the obtained slurry was separated into solid and liquid and dried to obtain the precursor Ni 0.5 Co 0.2 Mn 0.3 (OH)2.
[0144] The reaction process is as follows: in the reaction time period of 0 to 1h, the feed rate is controlled to be 8mL / min and the ammonia concentration is 15%; in the reaction time period of 1h to 10h, the feed rate is controlled to be 5mL / min and the ammonia concentration is 10%; in the reaction time period of 10h to 36h, the feed rate is controlled to be 1mL / min and the ammonia concentration is 2%.
[0145] It has been characterized that D2 / D1=10.
[0146] Comparative Example 1
[0147] This embodiment provides a ternary material. The preparation method of the ternary material is as follows:
[0148] S1. Precursor synthesis:
[0149] Mix nickel sulfate solution, cobalt sulfate solution, manganese sulfate solution and sodium hydroxide solution according to Ni 0.83 Co 0.12 Mn 0.05 (OH)2 was added to the reactor in a stoichiometric ratio; at the same time, an ammonia solution was introduced into the reactor. After reacting for 36 hours, the obtained slurry was separated into solid and liquid and dried to obtain the precursor Ni 0.83 Co 0.12 Mn 0.05 (OH)2.
[0150] The reaction process is as follows: in the reaction time period of 0 to 1h, the feed rate is controlled to be 8mL / min and the ammonia concentration is 15%; in the reaction time period of 1h to 10h, the feed rate is controlled to be 5mL / min and the ammonia concentration is 10%; in the reaction time period of 10h to 36h, the feed rate is controlled to be 1mL / min and the ammonia concentration is 2%.
[0151] S2, first sintering:
[0152] The precursor obtained in step S1 is mixed with lithium hydroxide in a molar ratio of 1:1, and sintered at 300° C. for 2 h, 500° C. for 5 h, and 800° C. for 15 h to obtain a sintered product.
[0153] S3, second sintering:
[0154] The sintered product obtained in step S2 is mixed with alumina to ensure that the molar ratio of Al / Mn is 0.02, and then sintered at 500° C. for 10 h and 200° C. for 4 h to obtain a ternary material.
[0155] It has been characterized that D2 / D1=10.
[0156] Comparative Example 2
[0157] This embodiment provides a ternary material. The preparation method of the ternary material is as follows:
[0158] S1. Precursor synthesis:
[0159] Mix nickel sulfate solution, cobalt sulfate solution, manganese sulfate solution and sodium hydroxide solution according to Ni 0.83 Co 0.12 Mn 0.05 (OH)2 was added to the reactor in a stoichiometric ratio; at the same time, an ammonia solution was introduced into the reactor. After reacting for 36 hours, the obtained slurry was separated into solid and liquid and dried to obtain the precursor Ni 0.83 Co 0.12 Mn 0.05 (OH)2.
[0160] The reaction process is as follows: during the reaction time period of 0 to 36 hours, the feed rate is controlled to be 1 mL / min and the concentration of ammonia water is 2%.
[0161] S2, first sintering:
[0162] The precursor obtained in step S1 is mixed with lithium hydroxide and yttrium oxide, and sintered at 800° C. for 15 hours to obtain a sintered product.
[0163] The molar ratio of the precursor to lithium hydroxide is 1:1, and the molar ratio of Y / Mn is 0.05.
[0164] S3, second sintering:
[0165] The first sintered product obtained in step S2 is mixed with alumina to ensure that the molar ratio of Al / Mn is 0.02, and sintered at 500° C. for 10 hours to obtain the ternary material.
[0166] It has been characterized that D2 / D1=1.
[0167] Comparative Example 3
[0168] This embodiment provides a ternary material. The preparation method of the ternary material is as follows:
[0169] S1. Precursor synthesis:
[0170] Mix nickel sulfate solution, cobalt sulfate solution, manganese sulfate solution and sodium hydroxide solution according to Ni 0.83 Co 0.12 Mn 0.05 (OH)2 was added to the reactor in a stoichiometric ratio; at the same time, an ammonia solution was introduced into the reactor. After reacting for 36 hours, the obtained slurry was separated into solid and liquid and dried to obtain the precursor Ni 0.83 Co 0.12 Mn 0.05 (OH)2.
[0171] The reaction process is as follows: during the reaction time period of 0 to 36 hours, the feed rate is controlled to be 1 mL / min and the concentration of ammonia water is 2%.
[0172] S2, first sintering:
[0173] The precursor obtained in step S1 is mixed with lithium hydroxide and yttrium oxide in a molar ratio of 1:1 (the molar ratio of Y / Mn is 0.05), and sintered at 300°C for 2h, 500°C for 5h, and 800°C for 15h to obtain a sintered product.
[0174] The molar ratio of the precursor to lithium hydroxide is 1:1, and the molar ratio of Y / Mn is 0.05.
[0175] Comparative Example 4
[0176] This embodiment provides a ternary material. The preparation method of the ternary material is as follows:
[0177] S1. Precursor synthesis:
[0178] Mix nickel sulfate solution, cobalt sulfate solution, manganese sulfate solution and sodium hydroxide solution according to Ni 0.83 Co 0.12 Mn 0.05(OH)2 was added to the reactor in a stoichiometric ratio; at the same time, an ammonia solution was introduced into the reactor. After reacting for 36 hours, the obtained slurry was separated into solid and liquid and dried to obtain the precursor Ni 0.83 Co 0.12 Mn 0.05 (OH)2.
[0179] The reaction process is as follows: during the reaction time period of 0 to 36 hours, the feed rate is controlled to be 1 mL / min and the concentration of ammonia water is 2%.
[0180] S2, first sintering:
[0181] The precursor obtained in step S1 is mixed with lithium hydroxide and yttrium oxide, and sintered at 800° C. for 15 hours to obtain a sintered product.
[0182] The molar ratio of the precursor to lithium hydroxide is 1:1, and the molar ratio of Y / Mn is 0.05.
[0183] S3, second sintering:
[0184] The first sintered product obtained in step S2 is mixed with alumina to ensure that the molar ratio of Al / Mn is 0.02, and sintered at 500° C. for 10 hours to obtain the ternary material.
[0185] After characterization, D2 / D1=25.
[0186] Test Case
[0187] 1. The ternary materials obtained in Examples 1 to 14 and Comparative Examples 1 to 4 were made into soft-pack batteries, and their discharge capacity, cycle number and cycle swelling were further tested. The performance test method is as follows:
[0188] The ternary material, conductive agent, polyvinylidene fluoride (PVDF) were mixed with N-methylpyrrolidone (NMP) in a mass ratio of 0.94:0.03:0.03 to prepare a positive electrode slurry (solid content of 70%), which was then coated on aluminum foil and baked at 120°C for 12h to obtain a positive electrode sheet; the positive electrode sheet was made into a 5Ah soft-pack battery cell to further test its performance.
[0189] (1) Discharge capacity test:
[0190] At 25°C, charge to 4.25V with 0.5C constant current, charge to 0.05C constant voltage, and then discharge to 2.5V with 0.2C constant current to obtain the gram capacity.
[0191] (2) Cycle number and gas production test:
[0192] At 45°C, charge with 1C constant current to 4.25V, charge with constant voltage to 0.05C cutoff, and then discharge with 2C constant current to 2.5V, and measure the initial gram capacity and initial battery cell thickness; cycle the above charge and discharge steps until the gram capacity is 80% of the initial gram capacity, and record the number of cycles and the battery cell thickness at this time.
[0193] Cyclic gas production is characterized by the change in cell thickness (Swelling ratio);
[0194] Cycle Swelling = (final cell thickness - initial cell thickness) / initial cell thickness * 100%.
[0195] The test results are shown in Table 1.
[0196] Table 1
[0197]
[0198]
[0199] It can be seen from Examples 1 to 3 that as D2 / D1 increases, the cycle performance and gas production are improved, and the gram capacity does not change much. It can be seen from Examples 2, 4, and 5 that the less the content of element Y, the smaller the improvement in cycle performance and gas production, and the effect on gram capacity is not obvious. It can be seen from Examples 2, 6, and 7 that the larger the Al / Mn (meaning the more shells), the better the cycle performance and gas production, but the gram capacity will decrease. It can be seen from Examples 2, 6, 7, 8, 9, and 10 that the larger the X2 / X1 (meaning that the high-valent elements in the shell are more doped), within a certain range, appropriately increasing X2 / X1 can increase the gram capacity, improve the cycle performance and gas production; but if X2 / X1 is too large, the gram capacity will decrease, and the cycle performance and gas production will not be further improved. It can be seen from Examples 2, 11, 12, and 13 that as X1 / Mn increases, the gas production is effectively improved, but the gram capacity will decrease, and the cycle difference is not significant. It can be seen from Examples 2 and 14 that low Ni content leads to reduced gram capacity. The ternary material of Comparative Example 1 does not contain high-valent elements, and the gas production is significantly deteriorated, and the cycle performance is deteriorated. The ternary material of Comparative Example 2 has no particle size gradient distribution, and the gram capacity, cycle performance, and gas production are all deteriorated. The ternary material of Comparative Example 3 has no alumina coating, and the cycle performance and gas production are significantly deteriorated.
[0200] 2. The ternary material obtained in Example 2 was ground for 10 min, 30 min, 60 min and 90 min respectively, the remaining main particles were screened out, and the Al and Y element contents in the ground powders were detected.
[0201] The results are shown in Table 2.
[0202] Table 2
[0203] Group Al content Y element content Grinding 10min 1145ppm 561ppm Grinding 30min 1024ppm 2271ppm Grinding 60min 890ppm 2145ppm Grinding 90min 776ppm 1998ppm
[0204] The embodiments of the present invention are described in detail above in conjunction with the embodiments, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.
Claims
1. A method for preparing a ternary material, characterized in that: The following steps are involved: S1. Adding an aqueous ammonia solution into a solution containing a nickel source, a cobalt source, a manganese source and a hydroxide source, and performing solid-liquid separation after the reaction to obtain a precursor; In the reaction, during the reaction time period of 0 to 1h, the feed rate is controlled to be 5mL / min to 10mL / min, and the concentration of ammonia water is 15% to 20%; during the reaction time period of 1h to 10h, the feed rate is controlled to be 2mL / min to 5mL / min, and the concentration of ammonia water is 5% to 10%; during the reaction time period of 10h to 36h, the feed rate is controlled to be 0.8mL / min to 1.2mL / min, and the concentration of ammonia water is 1% to 3%; S2, mixing the precursor with a lithium source and a first transition metal element source and performing a first sintering treatment to obtain a sintered product; The first transition metal element source includes at least one of a yttrium source, a niobium source, a molybdenum source, and a tungsten source; S3, mixing the first sintered product with alumina and performing a second sintering treatment to obtain the ternary material.
2. The preparation method according to claim 1, characterized in that: The molar ratio of the first transition metal element to the manganese element is 0.01 to 0.
3.
3. The preparation method according to claim 1, characterized in that: In step S3, the mixed preparation raw materials also include a second transition metal element source; Preferably, the second transition metal element source includes at least one of a yttrium source, a niobium source, a molybdenum source, and a tungsten source; Preferably, the molar ratio of the second transition metal element source to the first transition metal element source is 0.2 to 2.
5.
4. The preparation method according to claim 1, characterized in that: The lithium source includes at least one of lithium hydroxide, lithium carbonate and lithium nitrate; And / or, the nickel source includes at least one of nickel sulfate, nickel acetate, and nickel nitrate; And / or, the cobalt source includes at least one of cobalt sulfate, cobalt acetate and cobalt nitrate; And / or, the manganese source includes at least one of manganese sulfate, manganese acetate and manganese nitrate.
5. The preparation method according to claim 1, characterized in that: The reaction temperature of step S1 is 500°C to 1000°C.
6. The preparation method according to claim 1, characterized in that: The first sintering treatment includes sequentially treating at 250°C to 350°C for 1h to 3h, treating at 450°C to 550°C for 4h to 6h, and treating at 750°C to 850°C for 14h to 16h; And / or, the second sintering treatment includes sequentially treating at 450° C. to 550° C. for 9 h to 11 h and treating at 150° C. to 250° C. for 3 h to 5 h.
7. A ternary material, characterized in that: The ternary material is prepared by the preparation method according to any one of claims 1 to 6.
8. The ternary material according to claim 7, characterized in that: The ternary material comprises a core body and a shell layer arranged on the surface of the core body; the ratio of the primary particle size of the shell layer to the primary particle size of the core body is 5-20.
9. A positive electrode sheet, characterized in that: The ternary material comprises the ternary material as described in any one of claims 7 to 8.
10. Use of the preparation method according to any one of claims 1 to 6, the ternary material according to any one of claims 7 to 8, or the positive electrode sheet according to claim 9 in a lithium-ion battery.